2019
DOI: 10.3390/molecules24101929
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene as a Potential Protective Agent Against Myocardial Injury: The Role of Toll-Like Receptors

Abstract: Myocardial infarction (MI) remains one of the major causes of mortality around the world. A possible mechanism involved in myocardial infarction is the engagement of Toll-like receptors (TLRs). This study was intended to discover the prospective cardioprotective actions of β-caryophyllene, a natural sesquiterpene, to ameliorate isoproterenol (ISO)-induced myocardial infarction through HSP-60/TLR/MyD88/NFκB pathway. β-Caryophyllene (100 or 200 mg/kg/day orally) was administered for 21 days then MI was induced v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
1
41
1
Order By: Relevance
“…Oxidative stress plays an important role not only in AMI but also in many other cardiovascular disorders (17)(18)(19). Younis et al reported that ISO in a dose of 85 mg/kg bw decreased in P wave, QRS complex, PR segment, and RR intervals and increased in the QT interval duration and ST-segment deviation, in comparison with the control rats (20). According to results of Soraya et al rats from AMI group treated with ISO in a dose of 100 mg/kg bw showed a marked decrease in R-amplitude, a significant decrease in the RR interval and therefore, a significant increase in the heart rate (21 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important role not only in AMI but also in many other cardiovascular disorders (17)(18)(19). Younis et al reported that ISO in a dose of 85 mg/kg bw decreased in P wave, QRS complex, PR segment, and RR intervals and increased in the QT interval duration and ST-segment deviation, in comparison with the control rats (20). According to results of Soraya et al rats from AMI group treated with ISO in a dose of 100 mg/kg bw showed a marked decrease in R-amplitude, a significant decrease in the RR interval and therefore, a significant increase in the heart rate (21 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Group III (ISO) resembled group I, with the difference that the animals were injected (s.c.) with isoproterenol (85 mg/kg) on days 13 and 14 to induce MI. Groups IV (ISO plus geraniol 100) and V (ISO plus geraniol 200) included animals pretreated with geraniol that (either 100 or 200 mg/kg) [ 10 , 17 ] orally via gavage for two weeks and then injected with isoproterenol (85 mg/kg, s.c.) in days 13 and 14 for MI induction [ 22 ]. Geraniol (either 100 or 200 mg/kg) was always administered orally via gavage after dissolving in 1% carboxymethyl cellulose (CMC) in normal saline (1 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were anesthetized using urethane (1.5 g/kg) [ 22 ] at the end of the experiments and before euthanization, and then placed in a non-invasive computerized ECG apparatus (Kent Scientific, Torrington, CT, USA) to acquire ECG recordings as described previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,20,21]. Recent approval of β-caryophyllene as a food additive and flavoring agent by the Food and Drug Administration in the USA (FDA) and the European Food Safety Authority (EFSA) generated interest among the scientific community to explore its additional therapeutic benefits [22]. Numerous reports showed inhibitory effects of β-caryophyllene against bacteria, virus, and fungi [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%